Monologue: from criticism to the lyrics by N. Nekrasov (Eurasian Journal of Philology Science and Education, 2019)
The article deals with the issue related to the fact that Nekrasov, as a critic, has become a kind of link that ensures the continuity of the revolutionary-democratic tradition in Russian critical thought. The authors of the article stresse that Nekrasov’s critical articles are almost always less theoretical: he avoids reasoning of a general, abstract character, philosophical-aesthetic and simply philosophical digressions. The authors emphasize that N. Nekrasov’s critical works are almost always less theoretical: he avoids reasoning of a general, abstract nature, philosophical-aesthetic, and simply philosophical deviations. The work emphasizes the thesis that many critical articles and reviews by N. Nekrasov are related and organically linked with his own artistic practice. As a conclusion, it is argued that the critical activity of Nekrasov not only accompanied criticism of V. Belinsky or N. Chernyshevsky, but also compensated for certain aspects of their critical activities: corrected a number of one-sidedness characteristic of their critical judgments, sometimes had a direct impact on them with the help of monologue